Le dialogue socratique : un genre de référence de pratiques orales philosophiques à l'école primaire ? - Bettina Berton (Nantes Université, 2018)
Different practices of termed philosophical discussions have been developing in French primary schools for about fifteen years. Several recommendations of these practices refer to the type of discourse we call the socratic dialogue, thus reviving a former reference found in a few entries from the Buisson dictionary (1878-1887) ; the writers generally condemn this type but they use it as a reference when it comes to discussing the introduction of philosophy as a subject in the upper primary level. The didactic analysis of these two historical moments when the socratic dialogue is designed as a reference points out the theoretical weakness of the construction of this reference, not the least of which is the denial of its didactic transposition.